Atomic layer deposition and first principles modeling of glassy Li3BO3–Li2CO3 electrolytes for solid-state Li metal batteries. Issue 40 (3rd October 2018) - Kazyak, Eric; Chen, Kuan-Hung; Davis, Andrew L.; Yu, Seungho; Sanchez, Adrian J.; Lasso, Jose; Bielinski, Ashley R.; Thompson, Travis; Sakamoto, Jeff; Siegel, Donald J.; Dasgupta, Neil P.
Abstract : Glassy Li3 BO3 –Li2 CO3 ALD films are deposited and shown to have excellent stability against Li metal and high ionic conductivity. Abstract : Thin-film lithium solid electrolytes can serve as passivation layers, interfacial coatings, and enable 3D solid-state batteries. Here we present an Atomic Layer Deposition (ALD) process for synthesis of amorphous lithium borate-carbonate (LBCO) films. These films exhibit ionic conductivities up to 2.2 × 10 −6 S cm −1, six times greater than previously reported for any ALD solid electrolyte. First principles calculations trace the high conductivity to contributions from enhanced rotational motion of the carbonate and borate anions achieved by precise control of Li and C content by ALD. The high conductivity, coupled with a wide band gap and electrochemical stability window, leads to a total area specific resistance (ASR) of <5 Ω cm 2 for a 100 nm thick electrolyte and an ionic transference number >0.9999 from 0–6 volts vs. Li metal. The LBCO ALD solid electrolyte exhibits stability upon exposure to air, and in contact with both Li metal anodes and cathode materials. Thin-film full cells containing Li metal electrodes exhibit high coulombic efficiency for over 150 cycles with no capacity fading. These characteristics make glassy LBCO a promising new material for solid-state Li metal batteries.